Atmospheric particulate matter accumulation on trees: A comparison of boles, branches and leaves. (20th July 2019) - Xu, Xiaowu; Yu, Xinxiao; Mo, Li; Xu, Yansen; Bao, Le; Lun, Xiaoxiu
Abstract: A quantitative comparative analysis of PM accumulation on boles, branches and leaves is necessary to better understand the reduction of airborne PM by trees. This study compared the total water-insoluble particle accumulation mass per unit area, the distribution of water-insoluble particle size fractions, and the accumulation masses and compositions of water-soluble ions among different vegetative organs. The average accumulation capacity of water-insoluble particles was as follows: leaf epicuticular wax (11.1 ± 4.4 μg/cm 2 ), leaf surfaces (22.0 ± 3.2 μg/cm 2 ), terminal branch surfaces (101.6 ± 47.0 μg/cm 2 ), perennial branch surfaces (92.7 ± 20.0 μg/cm 2 ), and bark surfaces (1719.9 ± 684.7 μg/cm 2 ). Bole bark surfaces tended to accumulate the largest proportion of large particles, averaging 88 ± 4%. Branch surfaces and leaf epicuticular wax accumulated the largest proportions of fine particles, averaging 15 ± 5%. The total masses of water-soluble ions were 18 ± 10%, 33 ± 13% and 32 ± 6% of the total water-insoluble particles on boles, terminal branches and leaves, respectively. Leaf surfaces accumulated 2.2–6.0 times more SO2- 4 and NO 3 than did branch and bark surfaces. Graphical abstract: Image 1014832 Highlights: PM accumulation differed significantly among vegetative organs. Stem bark surfaces tended to accumulate large particles. Branch surfaces and leaf epicuticular wax accumulated more fine particles. Leaf surfaces accounted for greater proportion of water-soluble ions.